(2‐Vinyltetrazolyl)furoxans as New Potential Energetic Monomers. Issue 12 (13th December 2022) - Chaplygin, Daniil A.; Larin, Alexander A.; Meerov, Dmitry B.; Monogarov, Konstantin A.; Pronkin, Dmitry K.; Pivkina, Alla N.; Fershtat, Leonid L.
Abstract: A regioselective approach toward the synthesis of a set of new (2‐vinyltetrazolyl)furoxans as potential energetic monomers has been realized. All target energetic materials were thoroughly characterized by spectral and analytical methods. Moreover, crystal structures of two representative heterocyclic systems were studied by single‐crystal X‐ray diffraction. Prepared high‐energy substances have high combined nitrogen‐oxygen content (63‐71 %), high enthalpies of formation and good detonation parameters (D: 6.7–7.8 km s −1 ; P: 18–28 GPa). Mechanical sensitivities of the synthesized vinyltetrazoles range these explosives from highly sensitive to completely insensitive. Using calculations of molecular electrostatic potentials (ESP), structural factors influencing the impact sensitivity were revealed. Overall, newly synthesized (2‐vinyltetrazolyl)furoxans are of interest as promising energetic monomers due to the presence of the vinyl moiety and explosophoric heterocyclic combination, while their performance exceeds that of benchmark explosive TNT. Abstract : New energetic monomers : A set of new (2‐vinyltetrazolyl)furoxans as potential energetic monomers was prepared through the regioselective alkylation of the corresponding tetrazoles. Synthesized materials have good densities, high nitrogen‐oxygen contents and high enthalpies of formation. A combination of these parameters resulted in good detonation performance of all studied (2‐vinyltetrazolyl)furoxans exceeding that of benchmark explosive TNT.